Politeness In The Digital Spotlight: Analyzing Language Use In Deddy Corbuzier's 'close The Door' Podcast - Helmaliya, Erisa Putri; Andarwulan, Trisna; Panich, Pensri (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
Language plays a crucial role in social communication, including on digital platforms such as YouTube. One of the most popular podcasts in Indonesia,